2001
DOI: 10.1176/jnp.13.1.77
|View full text |Cite
|
Sign up to set email alerts
|

An EEG Severity Index of Traumatic Brain Injury

Abstract: EEG spectral analyses were conducted from 19 scalp locations for patients with mild (n=40), moderate (n=25), and severe (n=43) traumatic brain injury (TBI), 15 days to 4 years after injury. Severity of TBI was judged by emergency hospital admission records (Glasgow Coma Score and duration of coma and amnesia). Highest-loading EEG variables on each factor that differed significantly between severe and mild TBI by univariate t-test were entered into a multivariate discriminant analysis, yielding 16 variables. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…Quantitative features of brain electrical activity (QEEG) used in the BrainScope technology have also been shown to be sensitive to these changes in brain activity [12][13][14] without the limitations of other neuroimaging tools (e.g., availability at point of care, radiation exposure, cost-effectiveness). For example, the hypometabolism reported in PET imaging in TBI is consistent with slowing of the EEG spectra seen in this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative features of brain electrical activity (QEEG) used in the BrainScope technology have also been shown to be sensitive to these changes in brain activity [12][13][14] without the limitations of other neuroimaging tools (e.g., availability at point of care, radiation exposure, cost-effectiveness). For example, the hypometabolism reported in PET imaging in TBI is consistent with slowing of the EEG spectra seen in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The emergency medicine, neurosurgical and neuroscience literature indicates that the prevalence of structural brain injury visible on CT ("CT positive", CTþ) in adult patients with mTBI and Glasgow Coma Scale score (GCS) [4] of [13][14][15], evaluated in the ED ranges from 7.5% to 12.1% [5][6][7]. Several factors related to the status of the patients at the time of evaluation are important Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/cbm determinants in the prevalence numbers reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although specific qEEG findings vary between studies of persons with mTBI, among the most consistent findings are reduction in mean alpha frequency (Chen et al, 2006;Coutin-Churchman et al, 2003;Gosselin et al, 2009;Korn et al, 2005;Tebano et al, 1988;von Bierbrauer et al, 1992), increased theta activity (Fenton et al, 1993;Fenton, 1996;McClelland et al, 1994;Montgomery et al, 1991) or increased theta-alpha ratios (Chen et al, 2006;von Bierbrauer et al, 1992;Watson et al, 1995), reduced differences in alpha and beta power between anterior and posterior cortical regions, reduced alpha power posteriorly, and increased coherence and decreased phase between frontal and temporal areas (Thatcher et al, , 2001b(Thatcher et al, , 1989. Since abnormalities of these types are not etiology-specific (Coburn et al, 2006;Nuwer et al, 2005), efforts have been directed both at identifying combinations of qEEG panels that function usefully as neurodiagnostics for mTBI and also at exploring the relationship between qEEG abnormalities and the neurobiology of mTBI.…”
Section: Common Qeeg Findings Among Persons With Mtbimentioning
confidence: 99%
“…186,187 The importance of proper location and frequency band selection was also shown by Moore in a review of two OCD studies he conducted, where he found that pure alpha training did not produce any results. He concluded that this was because there were two OCD subgroups, neither of which would have been expected to benefit from alpha training.…”
Section: Treating Thought Disorders With Neurofeedback and Biofeedbackmentioning
confidence: 84%